INFORMATION REGARDING FIDUCIARY CONTRACTS AND THEIR LEGAL SPECIFICITIES - Ciprian Raul ROMIȚAN (Challenges of the Knowledge Society, 2018)
The sources of the fiducia are the law and the contract concluded in authentic form. Fiducia must be express and its running by an unilateral act or by judicial way is excluded. The fiduciary contract is an act conveyancing the ownership title, it is onerous, synallagmatic, commutative, intuitu personae and solemn. The fiduciary contract is the contract by which a party (the settlor), transmits as a trust to the other party (the trustee) goods and rights for the exploitation thereof for a determined purpose. Therefore, according to the provisions of the Civil Code in force, the parties to the fiduciary contract are the settlor (settlors) and the trustee (trustees). As one shall notice during out study, the beneficiary(-ies), the third party mentioned in the legal text defining the notion of fiducia, is not regarded as a party to the fiduciary contract. According to the author, the object of the fiducia supposes three successive stages of the complex contractual procedure: the transfer of patrimony rights from the settlor to the trustee, the actual management of the patrimony mass in the beneficiary’s favor, the transfer of the profit to the beneficiary, once or in successive stages. From the point of view of its legal nature, fiducia is a legal operation having as object the transfer of the property, receivable, security or other patrimony rights, whether existing or future, or a combination of such rights, to one or several trustees, exerting them in order to fulfill a determined purpose, in the favor or one or several beneficiaries. All these rights set up an patrimony mass distinct from the trustees’ other patrimony rights and obligations. As one could notice during the study, the fiduciary contract must comprise, under the sanction of absolute nullity, the following elements: real rights, receivable rights, guarantees and any other patrimonial rights transferred. In this regard, the transferred rights must be described in the fiduciary contract, by clearly indicating all identification elements; the period of the transfer, which cannot exceed 33 years as of the date of its conclusion; the identity of the settlor or settlors; the identity of the trustee or trustees; the identity of the beneficiary or beneficiaries or at least the rules allowing the determination thereof; the purpose of the fiducia and the scope of the powers of administration and disposition of the trustee or of the trustees.